Front Cover: Solar RRL 3‐4∕2017. Issue 3 (April 2017) - van Sark, Wilfried; Moraitis, Panos; Aalberts, Carlo; Drent, Max; Grasso, Thom; L'Ortije, Yves; Visschers, Marc; Westra, Mattijs; Plas, Rob; Planje, Wilko
Abstract : Luminescent solar concentrators consist of coloured plastic plates that concentrate sunlight to their sides where solar cells are mounted. Since their conception in the 1970s, novel dyes and nanocrystals have being developed for these concentrators, and it is time to show their full spectrum of colorful possibilities. In commemoration of the 100 th birthday of the art movement "De Stijl", of which the Dutch artist Piet Mondrian was a prominent member, van Sark et al. (article no.1600015 ) have developed a Mondrian‐inspired stained glass look‐a‐like window that serves as a solar energy harvesting device. It is based on luminescent solar concentrators, provides suffi cient power to charge mobile phones when placed in the windowsill and can also be used as an indoor decorative element. The authors describe in detail the design process of the "Electric Mondrian" and it is envisioned that similar designs will be deployed as building‐integrated photovoltaic elements.